2019
DOI: 10.1088/1361-6498/ab25be
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric issues with simplified homogeneous body models in low frequency magnetic field exposure assessment

Abstract: A simplified procedure, using circular disk models with homogeneous electric conductivity as representations for different body parts, has been proposed recently by product standard IEC 62822-3 for the assessment of magnetic field exposure in proximity to current-carrying conductors of welding equipment. Based on such simplified models, worst case coupling coefficients CCEi(I), i.e. maximum induced electric field strength, normalised for current and frequency, for body parts at different distances d to straigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The first problem that arises is deciding which of the evaluated quantities (maxE i,avg or a particular percentile) to use for the final decision. While it is recommended by the ICNIRP (2010) and the non-binding guide to 2013/35/EU (EU 2015a, 2015b) to use the 99th percentile of E i,avg , it has been repeatedly shown in the past that using p99.0 values can lead to a significant underestimation of actual exposure, especially in situations where exposure is highly localised (De Santis and Chen 2014, Schmid and Hirtl 2016, Gomez-Tames et al 2018, Schmid et al 2019b. Originally, it was argued that the use of p99.0 values eliminates numerical artefacts in the field distribution of the induced electric fields in tissue due to errors in the segmentation of the anatomical body models available at the time the ICNIRP (2010) guidelines were written.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first problem that arises is deciding which of the evaluated quantities (maxE i,avg or a particular percentile) to use for the final decision. While it is recommended by the ICNIRP (2010) and the non-binding guide to 2013/35/EU (EU 2015a, 2015b) to use the 99th percentile of E i,avg , it has been repeatedly shown in the past that using p99.0 values can lead to a significant underestimation of actual exposure, especially in situations where exposure is highly localised (De Santis and Chen 2014, Schmid and Hirtl 2016, Gomez-Tames et al 2018, Schmid et al 2019b. Originally, it was argued that the use of p99.0 values eliminates numerical artefacts in the field distribution of the induced electric fields in tissue due to errors in the segmentation of the anatomical body models available at the time the ICNIRP (2010) guidelines were written.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the uncertainty of the tissue conductivity data obtainable from the used database (Hasgall et al 2022) is also expected to contribute significantly to the uncertainty of the computed E i values. Worst case combinations of tissue conductivities (within the range of values reported in the mentioned database) for hand models lead to an increase of 90% of the maxE i,avg compared to the case when all tissues in the hand models were set to their average values reported in the database (Schmid et al 2019b).…”
Section: Uncertainty Considerationsmentioning
confidence: 99%
“…Clearly, the presented computational results in terms of maxE i,avg,peak have to be considered in the context of the underlying uncertainty. In Schmid et al (2019) different numerical hand/forearm models have been investigated concerning maxE i,avg,peak caused by magnetic field exposure, and variations of maxE i,avg,peak due to uncertainties of tissue conductivity and different spatial resolution of the computational grid have been investigated. They showed that even when considering extreme values of reported tissue conductivities leading to maximum conductivity contrast of adjacent tissues, the resulting increase in maxE i,avg,peak remains clearly less than a factor of two.…”
Section: Discussionmentioning
confidence: 99%
“…However, experimentally determined dB/dt threshold levels for the hands or even fingers have not been reported so far. In a recent publication Schmid et al (2019) reported induction factors (IF) of up to approximately 0.5 (V/m)/(T/s) obtained by numerical computations using anatomical models of human forearms exposed to a uniform magnetic field. Linking the IF of 0.5 (V/m)/(T/s) to the rheobase value for E i presently assumed in the range of approximately 4 to 6 V m −1 for the most sensitive myelinated nerve fibers (Reilly 1998, So et al 2004, a dB/dt threshold of at least 50-75 T s −1 can be estimated (equations (1) and (2)).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, anatomical models with a voxel resolution of 2 mm have been considered, and therefore the only 99th percentile has to be computed. Nevertheless, the 99.9th percentile is evaluated as well since the 99th percentile has sometimes been shown to underestimate the compliance, especially in the case of localized exposures [13,[25][26][27][28][29][30]. To better quantify these results, the values of the exposure assessment are summarized in Table 1, where E max is the peak induced electric field, whereas E 99.9 and E 99 are the 99.9th and 99th percentiles, respectively.…”
Section: Br Numerical Dosimetrymentioning
confidence: 99%